Design and Simulation of a Piezoresistive V-Shaped Strain Gauge for Torque Measring - Hilal, Muftah. M (Scientific Journal for Faculty of Science-Sirte University, 2021)
Modeling and simulation of system design adjustment is respectable training for design and engineering decisions in real world jobs. In this paper, the exact perseverance connected with the strain of components is very important for structural designs, analyses, and for excellent control. The information linked to this type of test is usually related to the exact dimensions connected with the pressure within a flexible region. This paper proposed the design and simulation of a torque sensor with a piezoresistive V-shaped strain gauge. The piezoresistive measure of a precious metal for a stable base was made according to the results of an ANSYS simulation. A torque sensor with a piezoresistive V-shaped tension measure on a base was made. The result of the particular simulation shifted the fraction of tension on the base to enable the torque on the substrate to be measured. Theoretical studies on the piezoresistive measure of a metal for the stable base as well as the torque sensor were introduced. A maximum of 127.29 με and a maximum resistance change in gauge equal to 0.091Ω were achieved for an applied torque of 22.0725 Nm. Here, computer systems modeling and simulation are going to be used.